Kesadaran Keamanan Konsumen dalam Penggunaan Transaksi Digital QRIS sebagai Perlindungan Konsumen Digital: Studi Kasus Penipuan QRIS pada Pedagang Pakaian di Kecamatan Kibin, Kabupaten Serang - Sri Lidya Agustin; Anita Fitri; Franoto Siswantoro; Faizal Alpiansyah (PT. Saha Kreasi Indonesia, 2025)
The development of digital transactions through the Indonesian Standard Quick Response Code (QRIS) payment system has boosted transaction efficiency, particularly in the micro and small business sector. However, the increase in QRIS usage has also been accompanied by a rise in digital transaction fraud cases, which are generally carried out through social engineering. One such QRIS fraud case occurred in Kibin Subdistrict, Serang Regency, affecting merchants who were users of digital transaction services. This study aims to analyze the forms of QRIS fraud and examine consumer security awareness in the use of digital transactions as part of digital consumer protection. The research method used is normative-empirical legal research with a regulatory and case study approach, supported by primary data in the form of interviews with three merchants who were victims of QRIS fraud. The results of the study show that QRIS fraud occurs not because of system failure, but rather due to low consumer security awareness and understanding of digital transaction mechanisms. Digital consumer protection in Indonesia is still oriented towards system security and has not optimally accommodated the aspect of user vigilance. Therefore, it is necessary to strengthen digital consumer protection that is not only technological in nature, but also based on increasing public security awareness.